The Krishna Cycle in the Puranas: Themes and Motifs in a Heroic Saga - K, Thomas (Journal of Dharma, 1984)
Benjamin Preciado Solis The Krishna Cycle in the Puranas (Themes and Motifs in a Heroic Saga) Motilal Banarsidass, Delhi, 1984, Pp 151 +74 plates, Rs 150-00